Host transcriptomic profiling of CD-1 outbred mice with severe clinical outcomes following infection with Orientia tsutsugamushi - Joseph Thiriot; Yuejin Liang; James Fisher; David H. Walker; Lynn Soong (Public Library of Science (PLoS), 2022)
Orientia tsutsugamushi is an obligately intracellular bacterium with endothelial tropism and can cause mild to lethal scrub typhus in humans. No vaccine is available for this reemerging and severely neglected infection. Previous scrub typhus studies have utilized inbred mice, yet such models have intrinsic limitations. Thus, the development of suitable mouse models that better mimic human diseases is in great need for immunologic investigation and future vaccine studies. This study is aimed at establishing scrub typhus in outbred CD-1 mice and defining immune biomarkers related to disease severity. CD-1 mice received O. tsutsugamushi Karp strain via the i.v. route; major organs were harvested at 2-12 days post-infection for kinetic analyses. We found that for our given infection doses, CD-1 mice were significantly more susceptible (90-100% lethal) than were inbred C57BL/6 mice (0-10% lethal). Gross pathology of infected CD-1 mouse organs revealed features that mimicked human scrub typhus, including pulmonary edema, interstitial pneumonia, perivascular lymphocytic infiltrates, and vasculitis. Alteration in angiopoietin/receptor expression in inflamed lungs implied endothelial dysfunction. Lung immune gene profiling using NanoString analysis displayed a Th1/CD8-skewed, but Th2 repressed profile, including novel biomarkers not previously investigated in other scrub typhus models. Bio-plex analysis revealed a robust inflammatory response in CD-1 mice as evidenced by increased serum cytokine and chemokine levels, correlating with immune cell recruitment during the severe stages of the disease. This study provides an important framework indicating a value of CD-1 mice for delineating host susceptibility to O. tsutsugamushi, immune dysregulation, and disease pathogenesis. This preclinical model is particularly useful for future translational and vaccine studies for severe scrub typhus. Author summary Scrub typhus is a severely neglected and potentially fatal disease caused by Orientia tsutsugamushi, a genetically intractable, obligately intracellular bacterium that annually infects at least one million people worldwide. There is no vaccine available, and our current understanding of the host immunological response and mechanisms remains very limited. Appropriate animal models of infection that recapitulate the disease are essential to the development of effective therapeutics and vaccines. In this study, we characterized the immunologic responses by transcriptomics and Bio-plex assays in outbred CD-1 mice with lethal O. tsutsugamushi infection. We found that CD-1 mice were highly susceptible to infection and that the high mortality correlated with a Th1/CD8-skewed, but Th2 repressed, immune profile during the acute phase of disease. This proinflammatory state was further confirmed by elevated cytokine and chemokine levels in the sera. Collectively, this study established CD-1 mice as a practical, preclinical model to define pathogenic mechanisms underlying severe scrub typhus and for future immunologic and translational studies during O. tsutsugamushi infection.